The Construction Industry: Outlook for 1930 - Clark, W. C. (The Review of Economics and Statistics, 1930)
W HEN the economist of the future compiles the business annals of the past decade, he will find the key to our prolonged and unprecedented prosperity in the stimulus provided by two great industries building construction and automobile manufacturing. Originally gaining momentum because of a long pent-up demand and then feeding upon the demand caused by the new wealth for which their own activities were primarily responsible, creating a market for the products of the iron and steel and other basic industries and providing employment directly or indirectlyin everyhamlet throughout the country, these two industries have constituted both the prime mover and the chief support of our recent prosperity. For the time being, however, this fruitful partnership in prosperity seems to have been dissolved. During 1929, while the building industry lost ground, slackening its pace some 12 or 13 per cent as compared with 1928, the automobile industry put on an astonishing burst of speed and left all its old records far behind. Today the overproduced condition in the motor industry is regarded by many as perhaps the sorest spot in the entire business situation, whereas the construction industry is now looked upon as the industry which will save us from business collapse, cushioning the decline in business activity and stimulating the forces of recovery. Will construction be able to play this role effectively? This is the crucial question which any forecaster of the new year's business must answer. In this brief summary we can only touch upon the three important favorable factors, (i) the readjustment which has already taken place in the building industry, (2) the stimulus of easy money, and (3) the prompt and aggressive mobilization, under the inspiration of President Hoover, of the campaign to use construction as a balance wheel of industry. The stimulating effect of these three forces will be somewhat retarded by (i) the loss of savings and paper profits in the stock market debacle, (2) the present condition of the savings banks, the building and loan associations and certain other lending institutions, and (3) the fact that supply and demand conditions in some branches of the building industry have not been entirely readjusted. The industry will be affected also of course by the general business situation, being retarded by continuing recession or stimulated by sustained activity, whichever may develop. The level of building costs will be a comparatively unimportant factor, though such influence as it exerts should be favorable, as lower prices for certain building materials, probable increased efficiency of labor in a depressed labor market, and lower money rates should tend toward lower construction costs. In the first place, it is clear that the substantial decline in building volume which took place during 1929 and which, in so far as residential building is concerned, extended over a much longer period has been extremely fortunate. This slowing down has enabled the industry to correct many of the excesses which had developed in the last six or seven years of unprecedented construction activity, but, coinciding as it did with unusual activity in the automobile and many other industries, its depressing effect upon general business was largely counteracted. The readjustment whichwe are nowexperiencing in general business, may be sharp enough; it would be more acute and more protracted had it not been for the year's start gained by the construction industry. However, though it has already made much progress, the building industry has by no means completed its readjustment process. In certain localities there still exists an overproduction of certain kinds of building facilities which must be largely absorbed before these types of construction can resume their usual activity. The extent to which the various classes of building activity will be affected during 1930 by existing surpluses of space will be discussed in a later section of this paper. The second favorable factor, easy money, will undoubtedly exert a powerful influence making for the resumption of normal activities in the industry. Comparison of building volume with bond yields, commercial paper rates, or other indexes of the cost of money over the past ten years reveals a high inverse correlation. Cheap